A comparison of data competencies among practitioners in the Malaysian construction industry - Lim, Ai Ling (2022)
The fourth industrial revolution is the trend towards automation and data exchange in technologies and processes. Consequently, data competencies become one of the important competences in demand. The literature search shows there is lack of study of data competences of construction industry practitioners. This research intends to bridge the gap by conducting an empirical study on the current data competencies among the construction practitioners. The objectives of this research include: exploring the data competence requirements in construction industry; evaluating the overall data competencies of the construction industry practitioners and analysing data competencies among different construction practitioners. Six data competencies, namely data fundamental, data generating, data filtering, data analysing, data modelling and data security and ethics have been synthesised from the literature reviewed. Questionnaire surveys were distributed to evaluate the data competencies level among the Malaysian construction industrial practitioners on the six data competencies was conducted. The results of 116 participants revealed that Data Security and Ethics, Data Fundamental and Data Filtering are the top three competence acquired and mostly applied by practitioners in construction industry. Developers are more competent in Data Fundamental compared to those providing consultation services. Architects are competent in Data Security and Ethics and Data Fundamental, Engineers are least competent in Data Fundamental, whereas Quantity Surveyors are least competent in Data Security and Ethics. Data Filtering and Data Analysing are frequently used by those working experience less than 3 years. Practitioners under 25 years are more frequently used Data Security and Ethics in industry. This conclusion was beneficial for academic institution to focus on the course curriculum design and the industry to plan for the training and retraining of their workforce. It also provided an indication to the regulatory agencies to direct their policies to support the data competences development of human resources in the construction industry.